Nitrogen fertilization strategies, morphogenetic and structural features in Brachiaria decumbens deferred for 95 days - Teixeira, Fábio Andrade; Pires, Aureliano José Vieira; Silva, Fabiano Ferreira; Fries, Daniela Deitos; Rezende, Claudia de Paula; Costa, Alexsandro Cotrim Pimentel Ribeiro; Santos, Thiago Cardoso; Nascimento, Paulo Valter Nunes (Semina: Ciências Agrárias, 2014)
The aim this work was to evaluate the morphogenic and structural characteristics of Brachiaria decumbens pastures to determine the most suitable nitrogen fertilization strategies, for pastures deferred for a period of 95 days. Four strategies of fertilization at the beginning and end of the summer (0-0, 100- 0, 50-50, 0-100 kg ha-1 N) were studied, respectively, with four replications. The strategy of 100 kg ha-1 N applied at the end of the summer (0-100), followed the parceling strategy at the beginning and end of the summer (50-50) favored higher rates of leaf appearance and lower values of phyllochron. Greater rate of leaf elongation was observed for 0-100 strategy, resulting in 40% increase compared to pastures that were not fertilized. However, there was no effect of fertilization strategies on stem elongation rate, registering an average of 0.28 cm.dia-1. There was a higher blade:stem ratio for the stratum A (40 cm above the soil) in all treatments, observing higher blade:stem ratio for strategies 0-100 and 50-50, at this stratum. There was no effect for the total number of leaves and final leaf length. However, greater stem lengths were observed in pastures with 0-100 fertilizer strategy, followed by the 50-50 strategy. The strategy of applying 100 kg ha-1 at the end of summer, followed by the strategy of 50 kg ha-1 nitrogen divided at the beginning and end of summer, promote greater influence on the morphogenic and structural traits, in pastures deferred for 95 days.